2021
DOI: 10.2471/blt.20.270983
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of violence against women and children during COVID-19, Germany

Abstract: Objective To assess the prevalence and exacerbating factors of violence against women and children in Germany during the coronavirus disease 2019 pandemic. Methods We conducted a representative online survey with partnered women (18–65 years) between 22 April and 8 May 2020, when participants had been under lockdown for a month. We determined the prevalence of several forms of violence within the previous month using both direct elicitation and a list experiment. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 40 publications
3
77
1
12
Order By: Relevance
“…GD in aggression are not significant at baseline and for household characteristics (being the main provider, living with children, living alone). While previous studies have established strong evidence for an increase of domestic and cyberviolence during the pandemic ( Fraser, 2020 ; Perez-Vincent et al, 2020 ; Ebert and Steinert, 2021 ), we show that the pandemic facilitates the development of aggression particularly in men. Previous studies have found robust correlations of the applied aggression questionnaire with act-based violence ( Archer and Webb, 2006 ; Jurczyk and Lalak, 2020 ), and emerging evidence in neuroscience points to the rewarding properties and self-perpetuating nature of violent acts ( Nell, 2006 ; Elbert et al, 2010 ; Golden and Shaham, 2018 ; Golden et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…GD in aggression are not significant at baseline and for household characteristics (being the main provider, living with children, living alone). While previous studies have established strong evidence for an increase of domestic and cyberviolence during the pandemic ( Fraser, 2020 ; Perez-Vincent et al, 2020 ; Ebert and Steinert, 2021 ), we show that the pandemic facilitates the development of aggression particularly in men. Previous studies have found robust correlations of the applied aggression questionnaire with act-based violence ( Archer and Webb, 2006 ; Jurczyk and Lalak, 2020 ), and emerging evidence in neuroscience points to the rewarding properties and self-perpetuating nature of violent acts ( Nell, 2006 ; Elbert et al, 2010 ; Golden and Shaham, 2018 ; Golden et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 64%
“…Indeed, this has previously been claimed to be a major health concern during the pandemic ( Bradbury-Jones and Isham, 2020 ; Telles et al, 2020 ), who argued that the impact of the pandemic has fueled stress and tensions within families, with an increased and continuous risk of domestic violence and divorce cases ( Chang, 2020 ; Peterman et al, 2020 ; Usher et al, 2020 ). Accordingly, several studies reported that the increase of domestic violence occurred especially during stricter lockdowns or states of emergency ( Campbell, 2020 ; Usher et al, 2020 ), e.g., a 55% increase of calls made to a domestic violence hotline during the lockdown in Argentina ( Perez-Vincent et al, 2020 ), or the reported increased risk of domestic violence during the pandemic in Germany ( Ebert and Steinert, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress, anxiety and depression or threats to livelihoods during the pandemic can increase the risk of violence against children by caregivers and are also known risk factors for intimate partner violence. 26 28 The COVID-19 pandemic has limited caregiver’s access to health workers, home-based parenting programmes, social services and social support. In response, efforts to support caregiver income, occupation and mental health should be prioritized.…”
Section: Addressing Violencementioning
confidence: 99%